Advances in pharmacotherapy for secondary hyperparathyroidism. (August 2015) - Rodríguez, Mariano; Rodríguez-Ortiz, María E
<x xml:space="preserve">Abstract</x> Introduction: Secondary hyperparathyroidism is a frequent complication of chronic kidney disease. This review will discuss the various therapeutic options available for the management of hyperparathyroidism. Areas covered: The main therapeutic strategies available to prevent or slow down the progression of hyperparathyroidism will be detailed here. Reductions in phosphatemia may be achieved by controlling dietary phosphorus, administering phosphorus binders, or increasing the frequency of dialysis sessions. Vitamin D sterols reduce parathyroid hormone (PTH) secretion while normalizing calcium (Ca) and vitamin D levels. Calcimimetics decrease PTH levels, probably with an additional effect on hyperplasia. Percutaneous injections in parathyroids represent an option useful in cases of hyperparathyroidism resistant to pharmacological therapy. Pubmed was searched by combining the terms 'secondary hyperparathyroidism' and the name of each one of the drugs reported in this review. Expert opinion: PTH increases from early stages of renal disease. One of the goals in pre-dialysis is the prevention of hyperphosphatemia and the maintenance of Ca levels in the normal range. The management of hyperparathyroidism in dialysis requires control of phosphorus level. In this stage, the decision to use calcimimetics and vitamin D derivatives should be made according to serum levels of Ca and phosphorus.